A Dancer in the Revolution : Stretch Johnson, Harlem Communist at the Cotton Club - Johnson, Howard Eugene, 1915-2000 (Book collections on Project MUSE., 2014)
Discusses the life of Howard ""Stretch"" Johnson, an African American civil rights activist and educator, (1915-2000), who was a dancer at the Cotton Club in Harlem, member of the Communist Party U.S.A. and World War II veteran.